Tingkat Risiko Psikologis Karyawan ATC di Salah Satu Cabang Air NAV Indonesia - Lalu Muhammad Saleh (Media Kesehatan Masyarakat Indonesia, 2018)
Air Traffic Controller (ATC) is a profession that serves as an air traffic guide who has a high level of stressin work. ATC works put forward the brain so that mental burden can occur. This study aims to see how far the levelof psychological risk factor ATC in work and hazard what causes it. The sample of research is ATC employees inMakassar Air Traffic Service Center which amounted to 35 people. Data collection using questionnaire and riskmeasurement using risk assessment matrix according to AS/NZS 4360 standard. The results showed that the highestlevel of risk that could affect the psychological aspects in work is due to work patterns 3 working days 1 restday, the lack of number of friends in work, number of planes observed, cold temperatures. The conclusion of thestudy was that ATC employees had psychological risks due to the work pattern 3-1, lack of friends, large numbersof aircraft, and cold temperatures. It is advisable to the management to immediately increase the amount of ATCpower, and provide work clothes as a protector of cold temperatures.